Contribution of Saharan Dust to Ion Deposition Loads of High Alpine Snow Packs in Austria (1987–2017) - Greilinger, Marion; Schauer, Gerhard; Baumann-Stanzer, Kathrin; Skomorowski, Paul; Schöner, Wolfgang; Kasper-Giebl, Anne (Frontiers in Earth Science, 2018)
We investigate the influence of Saharan dust (SD) on the chemical composition and deposition loads of a 31-year long snow chemistry data set (1987 to 2017) of high alpine snow packs situated close to the Sonnblick Observatory, a global GAW (Global Atmospheric Watch) station, in the National Park Hohe Tauern in the Austrian Alps. Based on the snow pack of the winter accumulation period 2015/2016, when two SD events were visible by a reddish color of the snow, we define a pH >5.6 together with a Ca2+ concentration >10µeq/l as thresholds to identify SD affected snow layers (= Saharan Dust Layers, SDLs). This criterion is checked with an intercomparison with trajectories and on-line aerosol data determined at the Sonnblick Observatory. This check was extended to the accumulation periods 2014/15 and 2016/2017 before the whole time series is investigated regarding the contribution of Saharan dust to ion deposition loads. Especially Mg2+, Ca2+ and H+ depositions are strongly affected by SD input causing as average values across the 30 years period increased Mg2+ (25%) and Ca2+ (35%) contributions of SDLs, while the contribution of SDLs to the snow water equivalent (SWE) was only 11%. For H+ SDLs show a much lower contribution (2%) while the contribution of other ions is well comparable to the deposition amount expected according to the SWE of SDLs. The pH range of SDLs covers 5.58 to 7.17, while the median value of all samples is 5.40. The long term trends of ion deposition are not affected by the deposition of Saharan dust.